Termos de parentesco nas línguas Tuparí (família Tupí) - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2019)
This article analyzes kinship terminology in the five languages of the Tupari branch of the Tupi family through two distinct approaches. First, the article compares kinship terms used in the Tupari languages and reconstructs ancestral Proto-Tupari forms for the main categories of consanguineous kin and in-laws. The five members of the Tupari branch possess clearly cognate terms which can be reconstructed for the proto-language of the family in various shared kinship configurations: grandparents (FF, FM, MF, MM), parents (M, F), aunts and uncles (MZ, MB, FZ), siblings (B, Z) and cousins (FBS, FBD), children (S, D), nieces and nephews (BS, BD, ZD, ZS), grandchildren (SS, SD, DS, DD), and affines (W, H, DH). Building upon the comparison of kinship terms within the contemporary Tupari languages and the ancestral forms reconstructed for Proto-Tuparí, these kinship systems are then discussed through the lens of anthropological theory, situating them within the theoretical developments in Amazonian kinship studies since 1990.
Kin terms in the Tuparian languages (Tupian family)
Keywords: Ramo linguístico Tuparí.; Terminologia de parentesco.; Reconstrução lexical.; Tupari linguistic branch.; Kinship terminology.; Lexical reconstruction.; CNPQ::CIENCIAS HUMANAS